Legal Liability Of Shipping Service Companies For Packaged Goods Owned By Consumers - Hanapi, Yayan; Nurmala, Leni Dwi (Universitas Negeri Gorontalo, 2022)
The development of the business world has progressed rapidly. This is seen in the use of delivery services. PT. The Nugraha Ekakurir (JNE) line is one of the services in the field of air traffic consignment services. The number of people sending goods from one place to another makes the role of this service very important. However, this is not accompanied by the provision of guarantees of legal protection by the perpetrators of entrusted services to their consumers. The implementation of JNE services needs to follow the agreement. So that it can cause harm to the consumers. The problem formulation is the legal protection for consumers and its resolution in case of negligence and delays in the delivery of goods. The method used is using normative legal research by conducting an assessment of the relevant legal rules. The results of the study showed that the services provided by the provider based on the agency cooperation agreement became the legal basis for the delivery of goods and still need to be improved and be more effective in providing guarantees for the rights of consumers. Quality service plays an essential role in creating satisfaction for consumers so that it can provide benefits for service providers.